The Daily Tail, 16 May 2017 - International Livestock Research Institute (International Livestock Research Institute, 2017)
Newsletter on end of conference highlights, the 7th Multi-Stakeholder Partnership (MSP) meeting of the Global Agenda for Sustainable Livestock, achieving multiple benefits through livestock-based solutions, May 2017